2022
DOI: 10.3390/ma15030925
|View full text |Cite
|
Sign up to set email alerts
|

3D Porous MXene (Ti3C2Tx) Prepared by Alkaline-Induced Flocculation for Supercapacitor Electrodes

Abstract: 2D layered MXene (Ti3C2Tx) with high conductivity and pseudo-capacitance properties presents great application potential with regard to electrode materials for supercapacitors. However, the self-restacking and agglomeration phenomenon between Ti3C2Tx layers retards ion transfer and limits electrochemical performance improvement. In this study, a 3D porous structure of Ti3C2Tx was obtained by adding alkali to a Ti3C2Tx colloid, which was followed by flocculation. Alkaline-induced flocculation is simple and effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…They displayed a specific capacitance of 300.2 F g À 1 at 1 A g À 1 and up to 400.7 F g À 1 after further annealing. [145] Wu et al found that strong proton acids can also trigger the three-dimensional assembly of Ti 3 C 2 T x nanosheets. As shown in Figure 9c, protons inhibit the ionization of À OH on the surface of Ti 3 C 2 T x and reduce the negative charge on the surface of Ti 3 C 2 T x nanosheets.…”
Section: Chemical Assembly Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They displayed a specific capacitance of 300.2 F g À 1 at 1 A g À 1 and up to 400.7 F g À 1 after further annealing. [145] Wu et al found that strong proton acids can also trigger the three-dimensional assembly of Ti 3 C 2 T x nanosheets. As shown in Figure 9c, protons inhibit the ionization of À OH on the surface of Ti 3 C 2 T x and reduce the negative charge on the surface of Ti 3 C 2 T x nanosheets.…”
Section: Chemical Assembly Methodsmentioning
confidence: 99%
“…obtained a 3D porous structure of Ti 3 C 2 T x by adding KOH to Ti 3 C 2 T x colloids for simple and effective flocculation within a few minutes. They displayed a specific capacitance of 300.2 F g −1 at 1 A g −1 and up to 400.7 F g −1 after further annealing [145] . Wu et al.…”
Section: Freestanding Flexible Mxene Composites For Supercapacitorsmentioning
confidence: 99%
“…In addition, the large specic surface area and the loose porous fold structure of poly(CTS-g-AM-MAPTAC) also enhanced its ability to catch and sweep the occulates in the late occulation period, making the generated occulation settle down quickly and improve the occulation efficiency. [36][37][38] Flocculation and sterilization of E. coli suspension. As with the kaolin occulation removal experiment, this section also examined the effect of occulant dosage, pH and graing rate of poly(CTS-g-AM-MAPTAC) on the removal of E. coli in wastewater.…”
Section: Performance Evaluationmentioning
confidence: 99%
“…In addition, the large specific surface area and the loose porous fold structure of poly(CTS- g -AM-MAPTAC) also enhanced its ability to catch and sweep the flocculates in the late flocculation period, making the generated flocculation settle down quickly and improve the flocculation efficiency. 36–38…”
Section: Bbd-rsm Optimized Synthesis Conditionsmentioning
confidence: 99%
“…2p 原子间轨道能级相差较大,轨道之间的杂化相对 较弱。因此,配体场分裂(10 Dq)相对于 d 轨道的 带宽较小,产生了金属能带结构,使得 MXene 具有 金属的性质 [21] 。 MXene 主要是通过形成 M-X 键调整 金属性质,同时导电性也受到它们的表面性质和形 态的极大影响 [22] 。MXene 的表面端接官能团-F 和-OH 基团的氧化态相似,只允许接收一个电子。而=O 基团的行为与之相反,在静止态占据了两个电子。 调整端接基团, 可以明显改变 MXene 的电子性质 [23] 。 MXene 的形态对电导率也有很大影响,单层和大尺 寸薄片比多层和小尺寸薄片具有更好的相互作用,; 通常会提高电导率 [24] 。与其他 2D 材料(如石墨烯或 金属硫化物/氢氧化物)相比, Ti3C2Tx 薄膜含有丰富的 官能团,有利于导电性 [25] 。 MXene 具有优异的导电性,确保了电子快速传 输,不仅可以实现高功率密度超级电容器,而且在 电极的制造过程中,甚至可以不用导电剂和集流体, 这有利于提高整个器件的能量密度 [26][27] 。在 可逆的电化学插层反应过程中,稳健的层间键合保 证了多层结构的稳定性。碳化物和氮化物 MXene 的 杨氏模量都随着层数 n 增加而降低。此外,氮化物 MXene 的层数 n 超过碳化物 [28] 。 机械性能会影响到电极的电化学性能,特别是 在未来的应用中,如在特定条件下,柔性电子器件 的电极会受到应力,发生弯曲和扭转,MXene 具有 优异的机械柔性,有助于保持良好的电化学性能, 便于其应用在柔性超级电容器和微型超级电容器中 [29] 。 2 MXene 的储能机理 [21] 。优化电解液或修饰表面端 基 T 对增强电容有一定的作用 [30][31][32] [21] 。 图 1 MXene 在( a)水系和(b)非水系 Li + 电解质中的结构变 化和电子结构变化示意图 [21] Fig nonaqueous Li + electrolytes [21] φ: inner potential; ηe: electron electrochemical potential 3 MXene 电极的纳米工程 [33] ,调节 MXene 的表面端基可有效改善其储能 性能 [34] 。改变合成环境(溶液类型、浓度、老化和 后处理),可以控制功能表面端基,改变 MXene 的 表面润湿性和亲水性质。在温和的蚀刻条件(稀 HF, H2SO4/HCl)下合成的 MXene 具有较好的热稳定性 和较低的缺陷密度。通常,碱化和退火 [35] 可以进一 步去除不利的表面基团,如-F 或-Cl。一旦端基被移 除,大量表面和边缘的金属原子可用来快速地进行 离子扩散,从而提高电导率,提升赝电容和倍率性 能 [36][37] 。 Li 等 [38]…”
unclassified